Evolution of the Asian summer monsoon during the Heinrich events 1-6 - Xue, Yan-Xia; Wu, Yao; Chen, Chao-Jun; Li, Jun-Yun; Cheng, Hai; Shen, Chuan-Chou; Zhang, Jian; Li, Ting-Yong (Global and planetary change, 2025)
There are still a series of controversies about the variation patterns and spatial differences of the Asian summer monsoon (ASM) during the Heinrich Stadials (HSs). Using stalagmite δ18O records from Yangkou Cave, Southwest China, this study revealed the climate dynamics of 6 weak ASM events corresponding to Heinrich events since the last glacial period. During the Asian Heinrich Stadial (AHS) 1-6, the ASM intensity in northern China responded rapidly to climate change in the North Atlantic, whereas the response in southern China was gradual. Ocean-atmosphere interactions under the bipolar “see-saw” mechanism dominated the ASM dynamics during the HSs. The ASM strengthening in the south of the Asian monsoon region was earlier and more gradual than in the north during the termination of the AHS, implying that the Southern Hemisphere high latitudes and tropical oceans played a critical role in the termination of millennial-scale abrupt climatic events. According to our observations, variations in moisture transport distances resulted in spatial differences in amplitude of stalagmite δ18O during the AHSs, implying that δ18O can reflect the hydrological imprint of variation in the ASM circulation.
Gesehen am 13.01.2026